Huella de carbono en el cultivo de la caña de azúcar. Evaluación agrícola de un caso de estudio de la amazonia ecuatoriana (2020)
Sugar cane is an economically important crop in Ecuador, in 2016 it represented 3.30% of the gross domestic product (GDP). It is considered a direct and indirect source of employment for around 110,000 inhabitants of the population. This work evaluates the emissions of Greenhouse Gases (GHG) from the production of sugarcane from a case study of the Ecuadorian Amazon. The methodology used is the Cool Farm Tool, based on the methods proposed by the Intergovernmental Panel on Climate Change (IPCC). The results of this study show that the production of a ton of sugar cane has a carbon footprint (HC) of 50 kg CO2 equivalent h-1. Direct and indirect field application of N2O and crop residue management were found to significantly affect greenhouse gas (GHG) emissions. The methodology used and the results obtained can be referential to study other agricultural extensions of sugar cane in the Ecuadorian Amazon. Finally, it is suggested that subsequent evaluations of products obtained with sugar cane be carried out to provide relevant information on the contribution.